Analisis Du Pont System Untuk Menilai Kinerja Keuangan Pada Perusahaan Subsektor Kosmetik Dan Keperluan Rumah Tangga Periode 2017-2020 Yang Terdaftar Di Bursa Efek Indonesia - Bintang Kusucahyo; Novalia Nur Hidayah (Akubis : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to analyze the financial performance of cosmetics and household goods sub-sector companies for the 2017-2020 period which are listed on the Indonesia Stock Exchange using the Du Pont System. The population in this study were six companies, samples were taken using purposive sampling method with predetermined criteria so that three companies were obtained using secondary data sources with quantitative descriptive data analysis. The results of the quantitative descriptive analysis show that the financial performance of PT Unilever Indonesia Tbk is better than that of PT Kino Indonesia Tbk and PT Cottonindo Ariesta Tbk because it has a higher and consistent ROE value every year.